Establishing the noise: interday ecological reliability of countermovement jump variables in professional rugby union players - Howarth, D. J.; Cohen, D. D.; McLean, B. D.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to examine the interday "ecological" reliability of a wide range of ground reaction force-derived countermovement jump (CMJ) variables. Thirty-six male, professional rugby union players performed 3 CMJs on 4 separate days over an 8-day period during the first week of preseason. We calculated reliability for 86 CMJ variables across 5 interday combinations using 2 criteria: mean output across 3 jump trials (Mean3) and single output from the highest jump (BestJH). Interday coefficient of variation (CV) of the 86 variables in each CMJ phase, for Mean3 and BestJH, respectively, ranged between concentric = 2-11% and 2-13%; eccentric = 1-45% and 1-107%; and landing = 4-32% and 6-45%. Mean3 interday CV was lower in all 86 variables across every interday combination, compared with BestJH. CVs were lower in our cohort than previous studies, particularly for eccentric phase variables. There was no meaningful difference between interday conditions, suggesting any 2-day combination conducted within the first 8 days of preseason, represents a measure of "noise." We did not apply arbitrary reliability "cut-offs" used in previous work (e.g., CV <10%); therefore, our analysis provides reference reliability for a wide range of CMJ variables. However, we recommend that practitioners assess reliability in their athletes, as it is likely to be environment, protocol, and cohort specific.